2023
DOI: 10.1002/qua.27274
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential of fluoro‐flavonoid derivatives as anti‐lung cancer agents: DFT, molecular docking, and molecular dynamics techniques

Nusrat Jahan Ikbal Esha,
Syeda Tasnim Quayum,
Minhaz Zabin Saif
et al.

Abstract: The present investigation utilized in silico methodologies to explore the diverse pharmacological activities, toxicity profiles, and chemical reactivity of a series of fluoro‐flavonoid compounds (1–14), which are secondary metabolites of plants known for their broad range of biological effects. A comprehensive strategy is utilized, incorporating methods such as prediction of activity spectra for substances (PASS) prediction, absorption, distribution, metabolism, excretion, and toxicity (ADMET) assessments, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 85 publications
(274 reference statements)
0
11
0
Order By: Relevance
“…[37] An equilibration process was conducted to ensure system stability, utilizing position-restrained dynamics (NVT) at 300 K for 3000 ps, implemented with the leapfrog algorithm. [12,13,38] Following this equilibration phase, the entire system underwent a production run for an additional 3000 ps under constant temperature and pressure conditions. Subsequently, the system was further simulated for 20 ns at the same temperature and pressure.…”
Section: Molecular Dockingmentioning
confidence: 99%
See 4 more Smart Citations
“…[37] An equilibration process was conducted to ensure system stability, utilizing position-restrained dynamics (NVT) at 300 K for 3000 ps, implemented with the leapfrog algorithm. [12,13,38] Following this equilibration phase, the entire system underwent a production run for an additional 3000 ps under constant temperature and pressure conditions. Subsequently, the system was further simulated for 20 ns at the same temperature and pressure.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…[10] Studies by Uddin et al [12,13] have shown that certain chemical derivatives have the potential to fight cancer. The first study [12] investigated benzylidinemalononitrile and ethyl 2-cyano-3-phenylacrylate derivatives, while the second [13] focused on fluoro-flavonoid derivatives. Both studies provide valuable insights into the anti-cancer properties of these compounds.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations